Report of a human accident caused by Conus regius (Gastropoda, Conidae) - Haddad Jr., Vidal [UNESP] (2009)
Conus regius is a venomous mollusc in the Conidae family, which includes species responsible for severe or even fatal accidents affecting human beings. This is the first report on a clinical case involving this species. It consisted a puncture in the right hand of a diver who presented paresthesia and movement difficulty in the whole limb. The manifestations disappeared after around twelve hours, without sequelae.